The prevalence of asthma among children in South Africa is increasing - is the need for medication increasing as well? A case study in the Vaal Triangle - Oosthuizen, M.A.; Mundackal, A.J.; Wright, C.Y. (Clean Air Journal, 2014)
Asthma, a chronic inflammatory condition of the airways, is a global public health concern. In southern Africa the prevalence of asthma has increased over the last few decades. In the current study, all 10-year-old learners from three of the schools (one each in Sasolburg, Vanderbijlpark and Vereeniging) that participated in the 1990 Vaal Triangle Air Pollution and Health Study, were selected as the study population for a cross-sectional study conducted in 2010. Both the 1990 and 2010 studies investigated several exposure factors but focussed on respiratory illnesses as main health outcomes. Although the overall ethnicity profile in 2010 was different from that of 1990, the socioeconomic status of the study populations were very similar – the reason being that the same schools were used and the participating children were from the same immediate environment. The results of the 2010 study were then compared to the results of all 10-year-olds, from the same three schools, who participated in the 1990 study. The results showed the difference in prevalence of asthma during the two study years was statistically significant. The difference in the percentage of children who had ever been diagnosed with asthma and were reportedly on medication in 1990 and 2010 was, however, not statistically significant, indicating that although the prevalence of asthma increased, the demand for medication to control the condition may not have increased as well.